Comparative analysis of combustion performance using pure and blended hydrocarbon fuels in a pulse detonation engine - Warimani, Mahammadsalman; Azami, Muhammad Hanafi; Alam, Noor; Khan, Sher Afghan; Patil, Suhas; Ramis, M. K. (Springer, 2025)
A pulse detonation engine (PDE) is a supersonic propulsive device used in aerospace vehicles. PDE employs periodic detonations to provide power or propulsion. In the present work, the Zeldovich–von Neumann–Doring (ZND) model is used to assess PDE performance for pure hydrocarbon and hydrocarbon-blended fuels. The combustion flame temperature ratio, detonation velocity, pressure ratio, and performance parameters like specific thrust and specific impulse are analytically calculated for various fuels. The novelty of the present research is the fact that thermophysical and performance characteristics of hydrocarbon fuels and of their blends have approximately the same results as given in the NASA Chemical Equilibrium with Applications (NASA CEA) data. All of the parameters' values fall within the acceptable range of the NASA CEA described values. The hydrocarbon fuels such as propane, butane, kerosene, and methane are safe, clean-burning, nontoxic, and great energy sources, and They are used as alternative hydrocarbon fuels in PDE.